Sensitive diagnosis of paucibacillary tuberculosis with targeted next-generation sequencing: a molecular diagnostic study - Yu Chen; Lichao Fan; Zhong Ren; Yanhong Yu; Jiao Sun; Miaoran Wang; Chang Liu; Ying Zhang; Shuihua Lu; Xuhui Liu; Zhen Huang (BMC Medicine)
Abstract Background Targeted next-generation sequencing (tNGS) enables high-performance tuberculosis (TB) diagnosis and drug resistance prediction directly from clinical samples. However, its applicability to paucibacillary TB, including pediatric TB and extrapulmonary TB (EPTB), has been less explored. We aimed to evaluate the performance of tNGS in these challenging TB presentations. Methods We prospectively and consecutively enrolled children (< 18 years) with suspected TB and adults with suspected EPTB. All participants underwent a comprehensive clinical examination, laboratory tests, and tNGS analysis. The diagnostic performance of tNGS was evaluated against composite reference standards, while resistance prediction capabilities were assessed with GeneXpert MTB/RIF and phenotypic drug susceptibility testing. Results A total of 85 children and 228 adults were enrolled. In children, tNGS showed a sensitivity of 74% (95% CI, 61–84%) and a specificity of 97% (95% CI, 84–100%) for microbiologically and clinically confirmed TB, whereas in adults with microbiologically and clinically confirmed EPTB, it demonstrated 77% sensitivity (95% CI, 68–83%) and 98% specificity (95% CI, 94–100%). For drug resistance prediction, tNGS exhibited variable sensitivity, peaking at 88% for rifampicin (95% CI, 47–100%) and bottoming out at 38% for streptomycin (95% CI, 9–76%), alongside a consistently acceptable specificity ranging from 89% (95% CI, 76–96%) to 100% (95% CI, 93–100%). Conclusions tNGS is a potentially promising test that enables rapid and sensitive diagnosis of TB in children and individuals with extrapulmonary TB. However, the variability in its accuracy for predicting drug resistance in these populations needs to be validated and addressed before its clinical application.